Food Supplement 20070721-GX May Increase CD34+ Stem Cells and Telomerase Activity. (22nd April 2012) - Lin, Po-Cheng; Chiou, Tzyy-Wen; Liu, Po-Yen; Chen, Shee-Ping; Wang, Hsin-I; Huang, Pi-Chun; Lin, Shinn-Zong; Harn, Horng-Jyh
Abstract : Few rejuvenation and antiaging markers are used to evaluate food supplements. We measured three markers in peripheral blood to evaluate the antiaging effects of a food supplement containing placental extract. Samples were evaluated for CD34 + cells, insulin-like growth factor 1 (IGF1), and telomerase activity, which are all markers related to aging. To control the quality of this food supplement, five active components were monitored. In total, we examined 44 individuals who took the food supplement from 1.2 months to 23 months; the average number of CD34 + cells was almost 6-fold higher in the experimental group compared with the control group. Food supplement intake did not change serum IGF1 levels significantly. Finally, the average telomerase activity was 30% higher in the subjects taking this food supplement. In summary, our results suggest that the placental extract in the food supplement might contribute to rejuvenation and antiaging.